PENGARUH APLIKASI HERBISIDA PADA SIMPANAN BIJI DALAM TANAH SAVANA BEKOL TAMAN NASIONAL BALURAN - Nurmuliayanti Muis; Titiek Setyawati; Soekisman Tjitrosoedirjo; Y. M. Diah Ratnadewi (CELEBES BIODIVERSITAS : Jurnal Sains dan Pendidikan Biologi, 2022)
The dominance of broadleaf weeds after A. nilotica control resulted in a decrease in the dominance of grass species in the savanna area of Bekol BNP. Herbicide application in controlling broadleaf weeds is an effective and efficient method. However, the impact of using herbicides on seed storage in the soil is unknown, while seed storage has an important role in the sustainability of vegetation. This study used a completely randomized factorial design with three factors, the factor was soil depth, the type of herbicide, herbicide concentration and control (without herbicide application). The effect of herbicide application on seed germination was analyzed by ANOVA. The results of this study indicated that the application of herbicides had no significant effect on seed germination in soil (P>0.05). So, the use of triclopyr and fluroxypyr herbicides could be considered as one of the measures in controlling broadleaf weeds in the Savama area of BNP.